Applying the Guess-the-Animal-Name Game Method in the IPAS Subject for Grade 3 at MI Nurul Islam Gedangmas, Randuagung Subdistrict - Maisiah, Silfia Aisatun; Hasanah, Adinda Shofiatul; Prayogo, Muhammad Suwignyo (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2023)
Learning through game-based methods is a crucial aspect of the learning process because it can create a dynamic learning environment, fostering an enjoyable, serious, and relaxed atmosphere. This research aims to implement the animal name-guessing game method as a teaching strategy in the IPAS subject for 3rd grade students at MI Nurul Islam. This game method is designed to enhance student engagement, reinforce understanding of animal concepts, and create a pleasant learning environment. The research adopts a qualitative approach to understand the phenomena related to the research subject in a natural context. Data sources encompass various types of information obtained by the researcher from the research subjects, who may act as respondents or informants. Data collection techniques include observation and interviews with teachers as the primary method to gather relevant information. Data analysis follows the model described by Miles and Huberman. The findings of this research indicate that the animal name guessing game method can be an effective alternative in improving IPAS learning in 3rd-grade classes at MI Nurul Islam. The implications of this research can serve as a guide for teachers and stakeholders in developing innovative and engaging teaching strategies to enrich students' learning experiences at the elementary education level.